Olive and its phenolic compound as the promising neuroprotective agent - Khidhir Kamil; Jaya Kumar; Muhammad Dain Yazid; Ruszymah Hj Idrus (Penerbit Universiti Kebangsaan Malaysia, 2018)
Recent progress in alternative medicine has highlighted the benefits of olive as an integral part of therapeutic diet to promote healthy living. Among the thirty different phenolic compounds of olive known to date; oleocanthal, oleuropein, tyrosol and hydroxytyrosol are being increasingly investigated for their potential in prevention and healing of several major forms of neurological dysfunctions and disorders. A considerable amount of literature suggests the neuroprotective effects of olive and its phenolic compounds are owing to their roles as anti-oxidant, anti-inflammatory and anti-apoptotic agents. At preclinical level, olive attenuated cognitive dysfunctions and the functional outcomes in spinal cord injury, delayed the progression of amyloid beta pathology, improved motor and mitochondrial dysfunctions in Parkinson’s disease, reversed diabetic-related neurological complications and also ameliorated cerebral pathologies in stroke. In this paper, we aim to review the neuroprotective role of olive and its phenolic derivatives in the following diseases or deficits of the nervous system that include cognitive dysfunction, neurodegenerative diseases, stroke, peripheral neuropathy and spinal cord injury.